A Computer-based Support for Participatory Management of Protected Areas: The SimParc Project - Briot, Jean-Pierre; Patto, Vinícius Sebba; Vasconcelos, Eurico; Sordoni, Alessandro; Adamatti, Diana; Irving, Marta de Azevedo; Melo, Gustavo; Alvarez, Isabelle; Lucena, Carlos (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA); 2009: Anais do I Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais, 2009)
In this paper, we introduce our current research project aimed at computer-based support for participatory management of protected areas, in order to promote biodiversity conservation and social inclusion. Its applicative objective is to help various stakeholders (e.g., environmentalist NGOs, communities, tourism operators, public agencies, and so on) to collectively understand conflict dynamics for natural resources management and to exercise negotiation management strategies for protected areas, one of the key issues linked to biodiversity conservation in national parks. Our approach combines techniques such as: distributed role-playing games, support for negotiation between players, and insertion of various types of artificial agents (decision making agents, virtual players, assistant agents). After a general introduction to the project we will present project’s current prototype architecture and results from game sessions, as well as some prospects for the future.